PENGGUNAAN APLIKASI ZOOM MEETING UNTUK EFEKTIFITAS PEMBELAJARAN DARING PADA MADRASAH IBTIDAIYAH MUHAMMADIYAH 01 PEKANBARU - Yuli Fitrisia; Kartina Diah Kusuma Wardhani; Mardhiah Fadhli; Wenda Novayani; Dini Nurmalasari; Sugeng Purwantoro ESGS; Memen Akbar (Jurnal Pengabdian Masyarakat Multidisiplin, 2021)
The pandemic that has hit the world has forced us to do learning indirectly or is often referred to as online (Daring). Online teaching and learning process requires some adjustments both on the teacher's side and the student's side. One of the adjustments is the need to seek technology and adaptation using technology. The currently widely used technology is online meeting services, such as the Zoom Meeting application, Google Meet, Video Calling via the Massager application, or other similar applications. To adapt to the technology, teachers at Madrasah Ibtidaiyah Muhammadiyah 01 Pekanbaru strongly desire to deepen ownership of the Zoom application as one of the media used for online learning. This training aims to provide an understanding and hands-on practice of using Zoom Meeting technology to increase learning effectiveness.